The Role of Protocol and Communication in Building President Joko Widodo's Leadership Image on Instagram - Ridho Karim Amrullah; Redi Panuju; Nurannafi Farni Syam Maella; Harliantara Harley Prayudha; Zulaikha Zulaikha (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research investigates how President Joko Widodo utilizes the social media platform Instagram to build a positive image at the end of his term of office. The research method used is discourse analysis, chosen because of its ability to reveal important linguistic aspects for understanding and interpreting content uploaded by President Joko Widodo (Jokowi) on the Instagram platform. The research results show that Jokowi consistently uses personalization and humanization strategies to strengthen his emotional relationship with society. The use of social media also emphasizes responsiveness to community aspirations and a focus on infrastructure development and social welfare. Attractive visual aesthetics have also proven to be a key factor in increasing the attraction and engagement of followers on President Joko Widodo's Instagram platform. Keywords: Social Media, President Joko Widodo, Public Image, Discourse Analysis